Pattern distribution and epidemic factors of stem canker disease caused by Neoscytalidium dimidiatum on pitahaya in Banyuwangi Regency, East Java, Indonesia - Andra Sahab Sukmana; Efi Toding Tondok; Suryo Wiyono (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Neoscytalidium dimidiatum is an airborne pathogen that causes stem canker disease, characterized by small brown spots surrounded by a yellow halo on the plant stem. These spots expand and darken from brown to dark brown and eventually black. In addition to attacking the plant stem, this disease can also infect the fruit. This research aims to understand the distribution pattern model of stem canker disease and to identify the factors contributing to the epidemic caused by N. dimidiatum. The study was conducted through the collection of secondary data, field observations of disease severity, assessment of farmers’ cultivation practices via questionnaires, isolation of phyllosphere and rhizosphere microbes, and soil chemical analysis. The results showed that this pathogen initially exhibits a random distribution pattern but later develops into infection patches with two possible dissemination modes based on the observed distribution pattern: airborne transmission and vegetative planting materials. Environmental factors influencing the stem canker epidemic include rainfall exceeding 98 mm/month, a temperature of 27 ºC, and humidity of 78.3%. Biotically, the diversity and abundance of phylloplane and rhizosphere microbes in low-severity areas are higher than in high-severity areas. From the abiotic aspect of soil chemistry, the elements P, Mg, Fe, and total N are associated with reduced stem canker intensity. Four aspects of cultivation techniques are closely related to the human role in the formation of the stem canker epidemic: the use of phytohormones, the control methods employed, the choice of pitahaya varieties, and yield losses.